Analisis Tingkat Pengetahuan Mahasiswa Program Studi Farmasi terhadap Swamedikasi Influenza - Yulnalia Mariella Delavega; Liza Pratiwi; Shoma Rizkifani (State University of Gorontalo, 2022)
The percentage of the population using self-medication to treat minor illnesses, such as influenza, continues to increase. Self-medication using over-the-counter drugs or without a doctor's prescription is not a completely safe treatment, so knowledge about the influenza and the drugs to be used is required. The purpose of this study was to determine the percentage of knowledge and behavior of self-medication for influenza, to determine the relationship between semester level and level of knowledge and behavior, and to determine the relationship between the level of knowledge and behavior of self-medication for influenza in Pharmacy students, Tanjungpura University. This method with a cross-sectional approach that is descriptive analytic. Respondents involved as many as 232 people including inclusion and exclusion criteria taken by stratified random sampling technique and the data were analyzed using Spearman rank correlation test. The results indicated that the respondents' knowledge level was good (39.7%), sufficient (50.0%), less (10.3%) and the respondent's behavior was right (96.6%) and inappropriate (3.4%). Relationship between semesters and the level of knowledge obtained sig (2-tailed) 0.000 and the value of r is 0.422; semester on the behavior of sig (2-tailed) 0.004 and the r value is 0.190; the level of knowledge on the behavior of the value of sig (2-tailed) is 0.007 and r is 0.178. The conclusion of this study is that the level of knowledge is in the sufficient category and the behavior is appropriate and there is a moderate undirectional relationship between semesters and the level of knowledge, a very low unidirectional relationship between semesters and behavior and there is a very low unidirectional relationship between the level of knowledge and behavior of influenza self-medication.